Model matching of input/state switched asynchronous sequential machines with the external switching signal - Hao, Xian-Zhi; Huang, Jin-Jie; Yang, Jung-Min (Nonlinear analysis. Hybrid systems, 2023)
This article investigates the input/state model matching problem of switched asynchronous sequential machines (ASMs) with the external switching signal in the framework of corrective control theory. The considered switched ASM is governed by the external switching signal that arbitrarily changes the mode of the switched ASM, prompting the active submachine into unpredictable state drift. We address the existence condition and design procedure for a proper corrective controller that matches the stable-state behavior of the closed-loop system to that of a reference model under any switching sequence. An illustrative example is provided for demonstrating the synthesis procedure of the proposed corrective controller. Compared with the prior work, the subject of this study is more challenging since rather than manipulated in favor of attaining model matching, the switching signal inflicts adversarial dynamic constraint that must be overcome by the controller. •Novel switched asynchronous sequential machine model with the external switching signal.•Mathematical framework for analysis of switched ASMs.•Model matching of switched ASMs under arbitrary switching signal.•Corrective controller overcoming adverse effects caused by switching operations.